Appraising choreographic creativity, aesthetics and the complexity of motor responses in dance - Castaner, M.; Torrents, C.; Morey G.; Jofre, T. (Mixed methods research in the movement sciences: Case studies in sport, physical education and dance, 2014)
Case Study 1: How to analyse dance choreographies: an illustration through contemporary works of Pina Bausch and Maurice Bejart Case Study 2: A study of motor creativity when dancing contact improvisation Case Study 3: The aesthetic appraisal of contemporary dance using a motion capture system